Ketamine in post-tonsillectomy pain - Erhan, Omer Luetfi; Goeksu, Huelya; Alpay, Cengiz; Bestas, Azize (Elsevier Ireland Ltd, 2007)
Objective: There has yet been no ideal method for postoperative analgesia in children. Ketamine demonstrates a potent analgesic effect by central blockage of perception of pain with sub-anesthetic doses. Preoperative intramuscular administration of ketamine for sedation decreases the pain during swallowing after tonsillectomy, while it provides tong-term analgesia when applied around the incision. The aim of this study is to compare the effectiveness of ketamine administered to the tonsillar region following tonsillectomy for postoperative pain management. Methods: After obtaining consent from the local. ethics committee and the parents, 60 patients from the ASA groups I and II, between 3 and 7 years of age, planned for adenotonsillectomy as outpatients, were included in the study. Subjects were randomly assigned to two equal groups and 2 ml. 0.9% saline for group S, and 0.5 mg kg(-1) ketamine and saline 2 mL in volume for group K were administered into the tonsillar region. All. subjects were monitored in a standard manner and SpO(2), systolic arterial pressure (SAP), and cardiac pulse rates were recorded in 5 min intervals. The CHEOPS and Wilson sedation scale were used to evaluate pain levels and sedative condition, respectively. Nausea and vomiting scores of the subjects were also noted. The time of the first analgesic administration and the total amount of analgesics in an 8-hour period were recorded. Student-T and Chi-Square tests were used for the statistical evaluation of the data and a p value of <0.05 was accepted as significant. Results: There were no significant differences between groups according to age, sex, weight, intermittent SAP and cardiac pulse rates. However, the CHEOPS value, the first analgesic need and the total amount of analgesic need were in favor of ketamine (p < 0.05). Conclusions: In previous studies, no significant differences were demonstrated in pre-emptive analgesia with ketamine, magnesium, morphine, and clonidine. The dose of ketamin and the volume used in this study caused no sedation or nausea and provided a high level of analgesia. Ketamine infiltration into the tonsillar region after tonsillectomy was found to be easy and effective. (C) 2007 Elsevier Ireland Ltd. Alt rights reserved.
Keywords: tonsillectomy; ketamine; analgesia